Pheromonally induced release of luteinizing hormone in male mice: involvement of the vomeronasal system - Coquelin, A (J Neurosci, 1984)
Evidence has accumulated demonstrating that the vomeronasal (accessory olfactory) system mediates intraspecific chemosensory communication in several mammals. For example, the neuroendocrine effects of priming pheromones in females and the behavioral responses to signaling pheromones in males are disrupted in mice with damage to the vomeronasal system. The experiment reported here examined the potential involvement of the vomeronasal system in the neuroendocrine reflexes observed in male mice following exposure to female and chemosensory stimuli. Excision of the vomeronasal organ (VNO) or sham VNO ablation was performed on sexually experienced males. Next, consecutive blood samples were withdrawn through chronic, intracardiac cannulas while the males were exposed to female mouse urine and then to an ovariectomized female. Plasma levels of luteinizing hormone (LH) were measured in the sequential samples by radioimmunoassay. Removal of the VNO did not affect the spontaneous pattern of episodic LH release that is characteristic of male mice. Reflexive release of LH following the urine stimulus was blocked in males lacking the VNO, but the female stimulus did cause LH responses in these mice. Our results therefore demonstrate that the VNO mediates pheromonally induced release of LH in male mice and that additional cues which emanate from behaving females also effectively stimulate a hormonal response in sexually experienced males.